The Palgrave Handbook of Toleration
eReference.
Keywords: The Palgrave Handbook of Toleration aims to provide a comprehensive presentation of toleration as the foundational idea associated with engagement with diversity. This handbook is intended to provide an authoritative exposition of contemporary accounts of toleration, the central justifications used to advance it, a presentation of the different concepts most commonly associated with it (e.g. respect, recognition) as well as the discussion of the many problems dominating the controversies on toleration at both the theoretical or practical level. The Palgrave Handbook of Toleration is aimed as a resource for a global scholarly audience looking for either a detailed presentation of major accounts of toleration, the most important conceptual issues associated with toleration and the many problems dividing either scholars, policy-makers or practitioners.